Dual-energy CT pulmonary angiography (DECTPA) quantifies vasculopathy in severe COVID-19 pneumonia - Ridge,CA; Desai,SR; Jeyin,N; Mahon,C; Lother,DL; Mirsadraee,S; Semple,T; Price,S; Bleakley,C; Arachchillage,DJ; Shaw,E; Patel,BV; et al. (Radiology: Cardiothoracic Imaging, 2020)
BackgroundThe role of dual energy computed tomographic pulmonary angiography (DECTPA) in revealing vasculopathy in coronavirus disease 2019 (COVID-19) has not been fully explored.PurposeTo evaluate the relationship between DECTPA and disease duration, right ventricular dysfunction (RVD), lung compliance, D-dimer and obstruction index in COVID-19 pneumonia.Materials and MethodsThis institutional review board approved this retrospective study, and waived the informed consent requirement. Between March-May 2020, 27 consecutive ventilated patients with severe COVID-19 pneumonia underwent DECTPA to diagnose pulmonary thrombus (PT); 11 underwent surveillance DECTPA 14 ±11.6 days later. Qualitative and quantitative analysis of perfused blood volume (PBV) maps recorded: i) perfusion defect ‘pattern’ (wedge-shaped, mottled or amorphous), ii) presence of PT and CT obstruction index (CTOI) and iii) PBV relative to pulmonary artery enhancement (PBV/PAenh); PBV/PAenh was also compared with seven healthy volunteers and correlated with D-Dimer and CTOI.ResultsAmorphous (n=21), mottled (n=4), and wedge-shaped (n=2) perfusion defects were observed (M=20; mean age=56 ±8.7 years). Mean extent of perfusion defects=36.1%±17.2. Acute PT was present in 11/27(40.7%) patients. Only wedge-shaped defects corresponded with PT (2/27, 7.4%). Mean CTOI was 2.6±5.4 out of 40. PBV/PAenh (18.2 ±4.2%) was lower than in healthy volunteers (27 ±13.9%, p = 0.002). PBV/PAenh correlated with disease duration (β = 0.13, p = 0.04), and inversely correlated with RVD (β = -7.2, p = 0.001), persisting after controlling for confounders. There were no linkages between PBV/PAenh and D-dimer or CTOI.ConclusionPerfusion defects and decreased PBV/PAenh are prevalent in severe COVID-19 pneumonia. PBV/PAenh correlates with disease duration and inversely correlates with RVD. PBV/PAenh may be an important marker of vasculopathy in severe COVID-19 pneumonia